Clinical profile of Herpes zoster in a rural tertiary care hospital in South India - Chankramat Sujatha Vinod; Hariharasubramony Ambika; Raghunath Nithya; Jayaprasad Sushmitha (Our Dermatology Online, 2014)
Introduction: Herpes zoster (Hz), which presents as localized, painful cutaneous eruption is a common clinical problem, particularly among adults of above 50 years of age and immunocompromised patients. It results from reactivation of varicella zoster virus. Aim: To analyze the clinical pattern of herpes zoster with special emphasis to the precipitating factors and incidence of post herpetic neuralgia. Material and Methods: 100 clinically diagnosed cases of herpes zoster, attending the Dermatology department of MVJ Medical College and Research Hospital Bangalore, India from a period of June 2010 to May 2012 were included in the study. The clinical pattern of herpes zoster with special emphasis to the precipitating factors and incidence of post herpetic neuralgia were analyzed. Results and Conclusion: The study showed a male preponderance. Age group varied from 8-80 years. 42% of the total patients presented during summer season when the incidence of varicella is also high. Past history of chicken pox was present in 68% of the patients. 11% of the patients were on immunosuppressive treatment. 8% of the patients had associated diabetes mellitus and 7% showed HIV seropositivity. Thoracic dermatomal involvement was seen in majority of patients. Most commonly observed complication was post herpetic neuralgia which was encountered in 36% of the patients and most of these patients were (77%) were above the age of 60years.